Trifid mandibular nerve canal - Mehmet Z Adisen; Melda Misirlioglu; Selmi Yilmaz (Wolters Kluwer Medknow Publications, 2013)
The location and configuration of the mandibular canal are important in surgical procedures involving the mandible. Bifid mandibular canal (BMC) and trifid mandibular canal (TMC) are variations of the normal anatomy. In the literature, occurrence of TMC is much rarer than BMC that only a few cases have been reported. These variations can be detected on a panoramic radiograph however more precise information about the course of the mandibular canal can be revealed on cross-sectional tomographic images. This paper presents a rare case of TMC evaluated by panoramic radiograph and CBCT. The main purpose of this case report is to pay attention to an apparently harmful anomaly, which can induce complications while surgical procedures.